CHEMICAL COMPOSITION AND GEOCHEMICAL FEATURES OF GORODSK GRANITES (ZHITOMIR REGION) - MATVIICHUK, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Pegmatites of Gorodsk granites are studied. The pegmatites consist of microcline, quartz, albite-oligoclase, muscovite, biotite with minor garnet, apatite, zircon and rutile. Columbite, zircon and apatite are studied and their crystallochemical formulas are given. The conclusions on the genesis of pegmatites are carried out.